2022
DOI: 10.1021/acs.est.1c07294
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Scaling and Wetting in Membrane Distillation: Mitigation Roles Played by Humic Substances

Abstract: Membrane scaling and wetting severely hinder practical applications of membrane distillation (MD) for hypersaline water/wastewater treatment. In this regard, the effects of feedwater constituents are still not well understood. Herein, we investigated how humic acid (HA) influenced gypsum-induced membrane scaling and wetting during MD desalination. At low concentrations (5–20 mg L–1), HA notably mitigated membrane scaling and wetting. The morphological characterization of scaled membranes revealed that the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The adsorbed SRHA molecules can also suppress gypsum crystallization by blocking the active growth sites and distorting the crystal morphology . In a study of combined fouling and scaling in MD, Wang et al observed a similar inhibitory effect of HA on the nucleation and crystallization of gypsum crystals. The authors measured the nucleation rate of gypsum in the bulk solution and observed that increasing HA concentration from 0 to 20 mg/L resulted in a gradual decrease in gypsum nucleation rate (Figure B).…”
Section: Mechanisms Of Mineral–organic Interactionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The adsorbed SRHA molecules can also suppress gypsum crystallization by blocking the active growth sites and distorting the crystal morphology . In a study of combined fouling and scaling in MD, Wang et al observed a similar inhibitory effect of HA on the nucleation and crystallization of gypsum crystals. The authors measured the nucleation rate of gypsum in the bulk solution and observed that increasing HA concentration from 0 to 20 mg/L resulted in a gradual decrease in gypsum nucleation rate (Figure B).…”
Section: Mechanisms Of Mineral–organic Interactionsmentioning
confidence: 99%
“…The authors demonstrated that all the foulants delayed and slowed water flux decline (Figure C), likely because the adsorption of foulants onto membrane surface obstructs gypsum crystallization . Moreover, Wang et al added various concentrations of HA to gypsum-supersaturated feedwaters for combined fouling and scaling experiments using direct contact MD, where the addition of HA mitigated gypsum scaling and enhanced water recovery. The authors explained that a HA foulant layer on the membrane surface enhanced the free energy barrier to gypsum nucleation .…”
Section: Presence Of Organic Foulants Alters the Behaviors Of Mineral...mentioning
confidence: 99%
See 3 more Smart Citations